Social Connectivity, Sentiment and Participation on Twitter during COVID-19. - Castro-Martínez, Andrea; Méndez-Domínguez, Paula; Sosa Valcarcel, Aimiris; Castillo-de-Mesa, Joaquín (MDPI, 2021)
In a transnational context defined by the irruption of COVID-19 and the social isolation it has generated around the world, social networking sites are essential channels for communicating and developing new forms of social coexistence based on connectivity and interaction. This study analyzes the feelings expressed on Twitter through the hashtags #YoMeQuedoEnCasa, #stayhome, #jeresteàlamaison, #restealamaison, #stoacasa, #restaacasa, #ficaemcasa, #euficoemcasa, #ichbleibezuHause and #Bleibzuhause, and the communicative and social processes articulated from network participation, during the lockdown in 2020. Through Gephi software, the aspects underlying the communicative interaction and the distribution of the network at a global level are studied, with the identification of leaderships, communities and connectivity nodes. As a result of this interaction, the emergence of social and organizational links derived from community participation and motivated by the common interest of preserving health and general wellbeing through collective action is detected. The study notes the presence of feelings of solidarity, a sense of community and social support among connected crowds who, despite being in geographically dispersed settings, share similar concerns about the virus effect.
Keywords: Pandemia de la Covid-19, 2020- - En los medios de comunicación social; COVID-19; Connectivity; Interaction; Participation; Sentiment; Social capital; Social media; Twitter